Effectiveness of Health Education Using Video and Poster Media on Elderly Knowledge About Hypertension - Doan Pratama; Lily Herlinah; Tria Astika Endah Permatasari (UIMA Press, 2024)
Background: The elderly, defined as individuals aged 60 years and above, have seen an increasing population due to advancements in healthcare but also face challenges such as hypertension. Hypertension, often referred to as